Interpersonal Stress Regulation and the Development of Anxiety Disorders: An Attachment-Based Developmental Framework - Nolte, Tobias; Guiney, Jo; Fonagy, Peter; Mayes, Linda C.; Luyten, Patrick (Frontiers in Behavioral Neuroscience, 2011)
Anxiety disorders represent a common but often debilitating form of psychopathology in both children and adults. While there is a growing understanding of the aetiology and maintainance of these disorders across various research domains, only recently have integrative accounts been proposed. While classical attachment history has been a traditional core construct in psychological models of anxiety, contemporary attachment theory has the potential to integrate neurobiological and behavioral findings within a multidisciplinary developmental framework. The current paper proposes a modern attachment theory-based developmental model grounded in relevant literature from multiple disciplines including social neuroscience, genetics, neuroendocrinology, and the study of family factors involved in the development of anxiety disorders. Recent accounts of stress regulation have highlighted the interplay between stress, anxiety and activation of the attachment system. This interplay directly affects the development of social cognitive and mentalizing capacities that are acquired in the interpersonal context of early attachment relationships. Early attachment experiences are conceptualised as the key organiser of a complex interplay between genetic, environmental and epigentic contributions to the development of anxiety disorders – a multifactorial aetiology resulting from dysfunctional co-regulation of fear and stress states. These risk-conferring processes are characterised by hyperactivation strategies in the face of anxiety. In the model, the cumulative allostatic load and subsequent “wear and tear” effects associated with hyperactivation strategies converge on the neural pathways of anxiety and stress. Attachment experiences further influence the development of anxiety as potential moderators of risk factors, differentially impacting on genetic vulnerability and relevant neurobiological pathways. Implications for further research and potential treatments are outlined.